Suicide Stigma as a Predictor of Help-Seeking Intention among Undergraduate Students in Jakarta - Prawira, Benny; Sukmaningrum, Evi (Makara Human Behavior Studies in Asia, 2020)
Previousresearch has found that stigma tends to impair help-seeking intention in a suicidal crisis for university students across the globe. Yet very little research has investigated how suicide-specific stigma affects help-seeking intention in a suicidal crisis amonguniversity students in the Indonesian context. This research examines the adverse relationship between suicide stigmaand help-seeking intention. A total of 284 university students in Jakarta, aged 18–24 years (M= 20.14, SD = 1.18), participatedin the study.Linear regression analysis demonstrated that suicide stigma positivelycontributes to the intention to seek help from both formal and non-formal sources. These resultscontradictprevious findings, possibly due to the unique culture in Indonesia.Theoretical and practical implications are discussed for Indonesian suicideprevention efforts.